The role of body weight for health, earnings, and life satisfaction - Olaf Hübler (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Based on the German Socio-Economic Panel, the influence of the body mass index on health, earnings and satisfaction is analysed by gender. Basic results are: health worsens, income declines and satisfaction is poorer with higher body mass index. If control variables are added, estimates are split by gender and different effects of over- and underweight people are determined, the health estimates show nonlinear effects but the direction of action is unchanged. Effects on earnings differ. Underweight women earn more and overweight less than others. For normal-weight men the income is on average higher than for over- and underweight men. This is also confirmed for self-employed persons. The pattern for employees is equal to the total sample. No effects on life satisfaction can be found except for underweight men. They reveal less satisfaction. Only in the public sector the sign of the coefficient changes. The results for eastern Germany are different with respect to satisfaction. Overweight women are less satisfied than others while this is not confirmed for underweight men from eastern Germany. When interdependencies are taken into account and matching procedures are applied, the outcome matches to that of independent and unmatched estimates. However, no clear-cut disadvantage in income of underweight men can be found. Stable coefficients result for the health estimates while satisfaction results fluctuate. Underweight women and especially underweight men tend to less happiness. For overweight men the influence is ambiguous but more speaks in favour of a less level of satisfaction. Overweight women seem to be happier.
Keywords: I15; I31; J16; J31; 330; over- and underweight; health; income; satisfaction; gender; self-confidence; wage earners vs. self-employed; private vs. public sector; eastern vs. western Germany; interdependencies; matching